2019
DOI: 10.1111/1440-1703.1007
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and stem traits variation of Stellera chamaejasme Linn. with slope aspect in alpine steppe

Abstract: Stellera chamaejasme L. is one of the dominant poisonous plant species and has caused considerable damage to the stability of grassland ecosystems and changed the structure and function of the grassland community, leading to grassland degeneration. To examine the response of morphological features of S. chamaejasme L. populations to environmental variations, leaf and stem traits were investigated in alpine grassland along the northern slope of the Qilian Mountains in northwestern China. Additionally, the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…The LS significantly increased in the NFS in our study (Figure 2b ) in accordance with other studies (Ackerly et al., 2002 ; Li et al., 2019 ). Ackerly et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The LS significantly increased in the NFS in our study (Figure 2b ) in accordance with other studies (Ackerly et al., 2002 ; Li et al., 2019 ). Ackerly et al.…”
Section: Discussionsupporting
confidence: 93%
“…The LS significantly increased in the NFS in our study (Figure 2b) in accordance with other studies (Ackerly et al, 2002;Li et al, 2019). Ackerly et al (2002) achieved a significant relationship of LS with irradiance along the slope gradient and suggested that the leaf temperature may be a constraining factor on SFS.…”
Section: Shifts Of Ls Along the South-north Slope Aspect Gradientsupporting
confidence: 92%
See 1 more Smart Citation
“…In woody communities, especially closed ones, self-shading among leaves reduces the efficiency of light interception by the lamina (Niinemets, 1998;Bell and Galloway, 2007;Roig-Villanova and Martíinez-Garcíia, 2016;Perez et al, 2018). Petiole elongation, at the expense of support, is one of the most obvious changes to diminish self-shading because it can send lamina to a higher position as well as adjust the angle of the lamina on a branch to avoid overlapping with its neighbors (King and Maindonald, 1999;Falster and Westoby, 2003;Bell and Galloway, 2007;Poorter and Rozendaal, 2008;Sarlikioti et al, 2011;Perez et al, 2018;Li et al, 2019;Zhong et al, 2019). The relationship between lamina length (LL) and petiole length (PL) is expected to be positive because of a higher proportion of overlap of longer laminas in a given space, which has been under genetic control (Tsukaya et al, 2002;Tsukaya, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Poisonous plant species are more e cient in utilizing N in poor nutrient soil than sedges and grasses, which may have been their survival mechanism in alpine grassland [28]. However, during the spreading of poisonous plants, self-reinforcing is a key driving force in degraded grassland [4,8,36], with the interaction of root exudates and rhizosphere microorganisms a key factor in the process [4,24,37]. We hypothesized that the exudate from roots of poisonous plant species contain more compounds for speci c microorganisms to promote self-growth than non-poisonous plant species.…”
Section: Introductionmentioning
confidence: 99%